Salai Guggul from Bostvellia serrata Roxb.-its Exploitation and Utilization - Murthy, T. Krishna; Shiva, M. P. (Indian Forester, 1977)
Utilization of salai guggul (gum-oleo-resin) from Boroellia serala Roxb. has been described. Method of tapping the tree for obtaining the product, keeping in view the wood structure in relation to distribution of gum-oleo-resin ducts haa been suggested. Information on method of collection, yield, processing, grading and market trend has been furnished. Nature and properties of gum-oleo-resin have also been briefly described.